Struktur Pertunjukan Kuda Lumping Di Kelurahan Kampung Lapai Kecamatan Nanggalo Padang - Rendi Alfajri; Marzam Marzam (FBS Universitas Negeri Padang, 2021)
This study aims to determine and describe the Performance Structure of Kuda Lumping in Kampung Lapai Village, Nanggalo District, Padang.This research belongs to a qualitative research. The research instruments used were the researcher it self, writing tools, and cellphone cameras. The object of this research was Kuda Lumping Brandon in Kampung Lapai Village, Nanggalo District, Padang.The results show that Kuda Lumping has a performance structure which cannot be removed or reversed from beginning to end. In the performance process, there must be several important people or instruments such as a handler, offerings, players, and other instruments such as musical instruments, properties, and a team which can help the handler in the process of Kuda Lumping show. Judging from the results of observations regarding the structure of the show, Kuda Lumping Brandon has a clear performance structure. It contains elements which are mutually related one to another. For instance, in term musical elements, if ini the lumping horse show there is no music, it will affect the dancer, this also related to the existence of a trance scene because each musical stroke will affect the movements of the dancer whose musical trance plays an important role in every lumping horse show without music, it will not have a beautiful aesthetic value.